Deciphering the Impact of a Bacterial Infection on Meiotic Recombination in Arabidopsis with Fluorescence Tagged Lines - Gratias, Ariane (Genes (Basel), 2020)
Plants are under strong evolutionary pressure to maintain surveillance against pathogens. One major disease resistance mechanism is based on NB-LRR (NLR) proteins that specifically recognize pathogen effectors. The cluster organization of the NLR gene family could favor sequence exchange between NLR genes via recombination, favoring their evolutionary dynamics. Increasing data, based on progeny analysis, suggest the existence of a link between the perception of biotic stress and the production of genetic diversity in the offspring. This could be driven by an increased rate of meiotic recombination in infected plants, but this has never been strictly demonstrated. In order to test if pathogen infection can increase DNA recombination in pollen meiotic cells, we infected Arabidopsis Fluorescent Tagged Lines (FTL) with the virulent bacteria Pseudomonas syringae. We measured the meiotic recombination rate in two regions of chromosome 5, containing or not an NLR gene cluster. In all tested intervals, no significant difference in genetic recombination frequency between infected and control plants was observed. Although it has been reported that pathogen exposure can sometimes increase the frequency of recombinant progeny in plants, our findings suggest that meiotic recombination rate in Arabidopsis may be resilient to at least some pathogen attack. Alternative mechanisms are discussed.